Strategi Penilaian Autentik (Authentic Assessment) dalam Pembelajaran Bahasa Indonesia pada Kurikulum Merdeka di Madrasah Ibtidaiyah - Reni Sangadah; Musrikah Musrikah; Chusnul Chotimah (Madrasah: Jurnal Pendidikan Madrasah, 2026)
Learning Indonesian in elementary schools or madrasah ibtidaiyah requires an effective approach to comprehensively assess students’ abilities. One method that can be applied is authentic assessment, which emphasizes evaluation based on real-world contexts and students’ practical skills. Authentic assessment is becoming increasingly relevant in the context of Indonesian language learning. The Merdeka Curriculum encourages a more flexible and contextual approach, so authentic assessment can play a significant role in enhancing students’ understanding. The objective of this study is to identify authentic assessment strategies to improve Indonesian language learning in elementary schools/madrasah ibtidaiyah. The methodology used in this study is a qualitative approach employing library research. The results of the study indicate that authentic assessment has great potential to improve the quality of Indonesian language learning in elementary schools. Realistic and contextual implementation encourages students to think critically and creatively. Support from various parties is needed so that authentic assessment can be implemented effectively and bring about positive changes in education in Indonesia.